The Millennium Development Goals and Production Engineering training - Jabbour, Charbel Jose Chiappetta [UNESP]; Jabbour, Ana Beatriz Lopes de Sousa [UNESP]; Filho, Walter Leal; Gunasekaran, Angappa (Emerald, 2015)
Purpose – The search for a more sustainable society depends on more sustainable organisations and, as such, Production (Industrial) Engineering may contribute to this process through the training of professionals with a greater social and environmental consciousness. The purpose of this paper is to present arguments in favour of the integration of Production Engineering and the Millennium Development Goals and evaluate the potential of Production Engineering subareas in contributing to the Millennium Development Goals. Design/methodology/approach – This work is conceptual and integrative in order to provide an original framework. A Brazilian perspective on Production Engineering has been adopted. Findings – A framework is proposed to guide this integration process by providing suggestions for an agenda of opportunities for academics and practitioners in favour of a more sustainable society. Originality/value – This work presents a new framework integrating Production Engineering and the Millennium Development Goals in order to promote a more sustainable training in Production (Industrial) Engineering field of research.
Keywords: Education for sustainable development; Industrial/Production Engineering; Millennium Development Goals; Sustainable development; Training for sustainable development